Effect of GNPs content on thermal and mechanical properties of a novel hybrid Cu-Al2O3/GNPs coated Ag nanocomposite. Issue 1 (January 2019) - Wagih, A.; Abu-Oqail, A.; Fathy, A.
Abstract: Hybrid Cu-Al2 O3 /GNPs coated Ag nanocomposites with GNPs content of 0%, 0.3%, 0.6%, 0.9% and 1.2% were successfully manufactured with improved mechanical and good electrical and thermal properties. Compressive strength, hardness, thermal and electrical properties were studied. The results indicated that compressive strength and hardness are significantly improved by increasing GNPs achieving 88.1% and 55.2% improvement, respectively. This improvement is attributed to the remarkable mechanical strength of GNPs, the reduction of grain size and the precipitation of GNPs on the grain boundaries of Cu. However, the coefficient of thermal expansion and electrical conductivity were reduced. Interestingly, increasing GNPs content has almost negligible effect of the thermal conductivity, at which the thermal conductivity is slightly reduced by a factor of 5% only by increasing GNPs content to 1.2%. These results highlight the advantage of reinforcing Cu-Al2 O3 nanocomposites by GNPs coated Ag for manufacturing hybrid nanocomposite with improved mechanical properties and good thermal conductivity.